2018
DOI: 10.1177/2331216518805352
|View full text |Cite
|
Sign up to set email alerts
|

Objective Binaural Loudness Balancing Based on 40-Hz Auditory Steady-State Responses. Part I: Normal Hearing

Abstract: Psychophysical procedures are used to balance loudness across the ears. However, they can be difficult and require active cooperation. We investigated whether 40-Hz auditory steady-state response (ASSR) amplitudes can be used to objectively estimate the balanced loudness across the ears for a group of young, normal-hearing participants. The 40-Hz ASSRs were recorded using monaural stimuli with carrier frequencies of 500, 1000, or 2000 Hz over a range of levels between 40 and 80 dB SPL. Behavioral loudness bala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…It is critical that clinicians ensure the programming of the device is optimized to facilitate the greatest possible improvement in hearing. CI programming involves selecting a current level that corresponds to the threshold level (T) and the most or maximum comfortable level (C or MCL) of hearing, thereby creating a dynamic range for each CI channel (Van Eeckhoutte et al 2018). Vaerenberg et al (2014) conducted a worldwide survey of CI programming procedures and found that 31% of clinics determined thresholds (Ts) only and set MCLs at intervals that were too high; 24% determined MCLs only and had Ts at 0 or 10%; while 45% determined both Ts and MCLs.…”
Section: Introductionmentioning
confidence: 99%
“…It is critical that clinicians ensure the programming of the device is optimized to facilitate the greatest possible improvement in hearing. CI programming involves selecting a current level that corresponds to the threshold level (T) and the most or maximum comfortable level (C or MCL) of hearing, thereby creating a dynamic range for each CI channel (Van Eeckhoutte et al 2018). Vaerenberg et al (2014) conducted a worldwide survey of CI programming procedures and found that 31% of clinics determined thresholds (Ts) only and set MCLs at intervals that were too high; 24% determined MCLs only and had Ts at 0 or 10%; while 45% determined both Ts and MCLs.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, symmetrical electrode positions were chosen on both the left and the right hemispheres, P4 and P8 in the RP region and P3 and P7 in the LP region [76]. This will remove the bias for a single hemisphere, which was indicated as a serious problem in several studies [77,78]. Locations P3, P4, Pz, P7 and P8 relate to perception and differentiation functions.…”
Section: E Electrode Placementmentioning
confidence: 99%
“…The rationale behind this channel selection strategy is to maintain symmetry. The symmetry criterion avoids bias to one hemisphere, which could be problematic as hemispheric differences are often found between subjects (e.g., Goossens et al, 2019; Van Eeckhoutte et al, 2018; Poelmans et al, 2012; Vanvooren et al, 2015). A similar channel selection strategy, also based on the utility metric, was proposed by Narayanan and Bertrand (2019) on an auditory attention decoding task, where the main goal was to optimize the topology of a wireless EEG sensor network (WESN), without imposing a symmetry constraint on the selected channels.…”
Section: Introductionmentioning
confidence: 99%